Efektivitas Bimbingan dan Konseling Klasikal Mahasiswa Prodi Pai STIT Al-Hilal Sigli Pada Siswa Kelas X SMK Negeri 1 Sigli: Effectiveness of Classical Guidance and Counseling for Students of Pai STIT Al-Hilal Sigli Study Program on Class X Students of SMK Negeri 1 Sigli - Teuku Amnar Saputra; Zuriah (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Motivation to learn is an important element and greatly influences student learning outcomes. The development of increasingly sophisticated technology does not always have a positive impact. At this time, many students become careless and have low motivation to learn because technology that is supposed to make things easier is misused. In the Guidance and Counseling discipline, one of the efforts that can be taken as a preventive measure against learning motivation problems is with Classical Guidance and Counseling services. Classical Guidance and Counseling is a service effort provided to students in one or a combination of several groups. The implementation of classical guidance and counseling services at the beginning of the 2023-2024 academic year was carried out using a collaboration system between students majoring in Islamic Religious Education (PAI) STIT Al-Hilal Sigli and guidance and counseling teachers at SMK Negeri 1 Sigli. The aim of this research is to find out the effectiveness of the Classical Guidance and Counseling services carried out by STIT Al-Hilal Sigli students at SMK Negeri 1 Sigli. This research uses a qualitative approach with descriptive methods. The data collection technique was carried out by observing the activities of classical counseling services and the enthusiasm of pupils and students. Then conduct interviews with school and student representatives. And study documentation on RPL and activity evaluation reports. Data analysis is carried out by reduction, presentation and drawing conclusions. The research results showed that the implementation of Classical Guidance and Counseling Services with the theme